2001
DOI: 10.2460/javma.2001.218.1281
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic changes in grossly normal menisci in dogs with rupture of the cranial cruciate ligament

Abstract: Histologic changes in meniscal cartilage correlate with gross appearance of the cartilage at time of surgery for rupture of the CCL. On the basis of minimal histologic changes, routine removal of grossly normal menisci does not appear to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
2
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 14 publications
2
68
2
6
Order By: Relevance
“…13,15 Despite the grossly normal appearance of menisci at this stage, these matrix changes initiate a cascade that subsequently leads to meniscal degeneration, gross fissuring and ultimately, complete maceration. 12 Results of an experimental study 14 in dogs indicated that the medial meniscus was grossly disrupted in 86% of cranial cruciate ligament-deficient stifle joints within 6 months.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…13,15 Despite the grossly normal appearance of menisci at this stage, these matrix changes initiate a cascade that subsequently leads to meniscal degeneration, gross fissuring and ultimately, complete maceration. 12 Results of an experimental study 14 in dogs indicated that the medial meniscus was grossly disrupted in 86% of cranial cruciate ligament-deficient stifle joints within 6 months.…”
Section: Methodsmentioning
confidence: 98%
“…[8][9][10][11] Secondary meniscal injuries occur weeks to months after rupture of the cranial cruciate ligament and are a consequence of craniocaudal subluxation of the femorotibial joint. [12][13][14][15] Meniscal injury may also be a complication that develops late after surgical reconstruction of the ruptured cranial cruciate ligament. 16 Most injuries of the medial meniscus involve the caudal pole, which may be torn from its capsular attachment and folded forward under the medial femoral condyle.…”
mentioning
confidence: 98%
“…As artropatias envolvendo o joelho estão entre as moléstias mais freqüentemente diagnosticadas na prática clínico-cirúrgica de pequenos animais, sendo a ruptura do ligamento cruzado cranial (LCCr) causa comum de claudicação dos membros pélvicos (PAYNE & CONSTANTINESCU, 1993;DECAMP et al, 1996;JACKSON et al, 2001).…”
Section: Introductionunclassified
“…With the evidence of meniscectomy causing the progression of osteoarthritis (OA), treatment of meniscal tears is towards to maximal preservation of meniscal tissue. Since damaged portions of the meniscus should be removed to avoid the progression of OA, maximal retention of grossly normal menisci is desirable [3]. However, it is difficult to ensure that the grossly normal portions are without any pathologic changes.…”
Section: Introductionmentioning
confidence: 99%